Pcngaruh Sudut Vertikal Terhadap HasH Ukuran Jarak dan Bcda Tinggi Metode Trigonometris Menggunakan Total Station Nikon DTM 352 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Abstract The measurement of heigh differences using trigonometric technique, and Total Station Nikon DTM 352 is used.It is identified that the use of different vertical angle will produce different heights for the same point. It is interesting to analyse further that, the errors of distance and height differences in trigonometric technique are as the function of vertical angle. This research tries to investigate the phenomenom mentioned above: is there sistimatical error? and how to corect them ? This research is initially arranged to include some steps: (1) preparation of instruments, (2) measurement of distance and height differences in study area using spirit levelling and trigonometric levelling, (3) Data processing including correction of differences in height modelling. Evaluation was carried out by comparing both data of observed height differences. Based on the result of the statistical test, it is found that the variety of vertical angles do not affect the computed distance and height differences using Total Station. From the data exercises resulted.. that the accuracy of height differences is affected by distance and vertical ~ngle, howeverfor the distance up to 800 m, the improvement is not signifcant. In addition the field observations also show that the distance greater than 50m , the contribution of the accuracy of angle to the change of the accuracy of height differences is greater than the contribution of the accuracy of the distances. Keywords: height differences, trigonometric levelling, trigonometric technique, Total Station.